1984
DOI: 10.1007/bf01439902
|View full text |Cite
|
Sign up to set email alerts
|

Probing sub-barrier fusion and extra-push by measuring fermium evaporation residues in different heavy ion reactions

Abstract: The production of fermium isotopes was attempted by complete fusion of different targets and projectiles spanning a wide range of effective entrance channel fissilities below and above the predicted threshold value Xef fthr~(l'/-v... For the most asymmetric systems where fusion is expected to occur without dynamical hindrance we investigate to what extent the expected amount of sub-barrier fusion contributes to the production of fermium evaporation residues. For increasingly symmetric systems the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 43 publications
6
42
0
Order By: Relevance
“…For the intermediate system 4~176 this new systematics [15] predicts an extra-push energy for formation of a compound nucleus inside the true fission saddle point of the order of 10 MeV. This is at variance with work by G/iggeler et al [20], who concluded on the basis of cross sections for fusion-evaporation residues [20] and for fission [22] that the 4~ Pb reactions did not show any evidence for an extra push.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…For the intermediate system 4~176 this new systematics [15] predicts an extra-push energy for formation of a compound nucleus inside the true fission saddle point of the order of 10 MeV. This is at variance with work by G/iggeler et al [20], who concluded on the basis of cross sections for fusion-evaporation residues [20] and for fission [22] that the 4~ Pb reactions did not show any evidence for an extra push.…”
Section: Introductionmentioning
confidence: 67%
“…From these observations and from the Z-dependent asymmetries we conclude that a significant fraction of the cross section for fission in the 4~176 reaction is due to quasi-fission reactions which do not involve compound-nucleus formation inside the fission barrier. As is evident from the observation of fusion-evaporation residues [20] true fusion followed by fission must be present as well. Thirdly, again in agreement with our previous findings for the reactions of S~ and S6Fe with 2~ [18], there are products from deep-inelastic scattering of 4~ from 2~ with atomic numbers close to Z=82 and sideward peaked angular distributions centered close to the grazing angle (0 = 55 ~ for targetlike products at Ecru = 172 MeV), see Fig.…”
Section: Z-dependent Asymmetries and Ko-valuesmentioning
confidence: 92%
See 2 more Smart Citations
“…As we have chosen identical or very similar compound nuclei in our comparative study between hot and cold fusion reactions, we should be able to deduce information on the possible influence of the fusion dynamics by comparison with experimental cross sections. One of the most spectacular experimental results of the lead based reactions, besides the discovery of the heaviest elements known today rl, 2], was certainly the fact that the 2n cross section, which was several nanobarn in the fusion of 4OAr+ z~ [43], was several microbarn following the fusion of ~SCa with 2~ [44] leading to an element (102) that has an atomic number 53 higher by two charge units. Could this be understood quantitatively?…”
Section: Results For Fusion Reactions Using Targets Around Pbmentioning
confidence: 99%